Resource characterization and utilization of Lepironia articulata (Retz.) domin at Kg. Beris Tok Ku And Kg. Beting Lintang, Terengganu / Shoma Tani - Shoma , Tani (2021)
This research focused on how handicrafts could contribute to sustainable community development with natural resource management. This research aims to characterize Lepironia articulata as a resource by taxonomy and distribution patterns, examine its utilization through group and semi-structured interviews with ten local residents who got involved in handicraft productions at two selected villages in Setiu Wetlands of Terengganu state and identify their capacity development opportunities by following a guideline provided by United Nations Development Programme. This research clarified that the height of Lepironia articulata in Setiu Wetlands was shorter than the records of the other description and the other site in Singapore while the width of stem and the bladeless sheaths were similar to former records. Lepironia articulata was utilized sustainably except for the coloring method during the material preparation process. Capacity of producers on information technology and weaving and making handicrafts skills could be further developed with collaboration of multi stakeholders and leadership of the state government.